Implementasi Metode Certainty Factor Untuk Mengidentifikasi Tipe Kepribadian Karyawan Toserba Luragung - Wahyu Ariandi; Ade Kurniawan (STIKOM POLTEK CIREBON, 2023)
This research was conducted with the aim of facilitating the selection of prospective new employees at Fajar Toserba Luragung by identifying the personality types of prospective employees. The personality test process for employee acceptance currently does not use an expert system. The advantage gained by using this application is that companies can find out the personality categories of prospective employees more easily and quickly compared to the previous method. This method will provide a solution to determine one's commitment to a company. An expert system is a computer program that tries to imitate or simulate the knowledge and skills of an expert in a particular area. Furthermore, this system will try to solve a problem according to its expertise. The certainty factor is a way of combining trust and disbelief. Qualitative data will be represented as a degree of confidence. The result is that an expert system with the Certainty Factor method can help the personnel department in identifying the personality type of prospective employees by 11.63%. This application can help the personnel department to find out the personality traits of prospective employees and find placement solutions that are suitable for new employees.